Pituitary Apoplexy After a Single Dose of Long-Acting Octreotide - Chang, Claudia Veiga [UNESP]; Felicio, Andre Carvalho; Nunes, Vânia dos Santos [UNESP]; Carneiro da Cunha-Neto, Malebranche Berardo; Barros de Castro, Ana Valeria [UNESP] (Lippincott Williams & Wilkins, 2010)
Pituitary apoplexy (PA) is a rare and potentially life-threatening syndrome resulting from an acute infarction or hemorrhage of the pituitary gland. Although the pathogenesis is not fully understood, some predisposing factors such as pituitary stimulation tests, diabetes mellitus, anticoagulant or antiplatelet aggregation therapy, head trauma, and high blood pressure may play a role in its pathophysiology. Octreotide is the mainstay of medical treatment for acromegaly. The majority of reported complications of octreotide therapy are gastrointestinal. We report the case of a 51-year-old acromegalic woman who developed pituitary apoplexy within the context of high blood pressure and a single dose of long-acting octreotide. Our data suggest that the combination of hypertension and octreotide therapy enhances the risk of pituitary apoplexy.
Keywords: acromegaly; pituitary apoplexy; octreotide; hypertension